Isolation and characterization of lytic bacteriophages for the composition of a phage cocktail capable of reducing bacterial biofilms in oil-related environments - Silva, Jéssica Duarte da (2023)
Phages are viruses that infect bacteria and since their discovery in the early 20th century, they have been used to control bacterial growth. This work was divided into three chapters. The first genomically and biologically characterizes the Enterobacter phage vB_EclM-UFV01, presenting general characteristics of its genus, the Karamviruses. Chapter 2, examines the capacity of a phage cocktail (composed by enterobacteria-isolated phages) to reduce the biofilm of sulfate-reducing bacteria. The formulation of the cocktail, named Petro01, was performed by selecting phages from the collection of the Laboratory of Molecular Immunovirology at UFV and ended up being composed of three phages of the Tequatrovirus genus (briefly characterized genomically in this chapter) and one of the Karamvirus genus (described in Chapter 1). The stability of Petro01 under conditions similar to those found in petroleum-related environments, its shelf life at high storage temperatures, the supernatant composition (LB enriched with conservative compounds), as well as the propagation capacity of the phages that make up the cocktail in bench and a 12 L bioreactor, was also evaluated. Petro01 showed significant biotechnological potential and positive capacity for the composition of a phage-based product. Chapter 3 moves away from the environmental application of bacteriophages and characterizes, biologically and genomically, the Proteus mirabilis phages BigMira UFV01 and MidiMira UFV02, providing an overview of the common features of their genus, the Acadeviruses. It also presents the genomic evaluation of 10 strains of P. mirabilis, isolated in clinical environments, focusing on the LPS locus and the antimicrobial resistance profile. All phages described in this study have good potential as antibacterial agents. Keywords: Bacteriophages. Industrial microbiology. Sulfate-reducing bacteria. Bioproducing.